A COMPARATIVE STUDY OF BIODIVERSITY CONSERVATION COPING WITH CLIMATE CHANGE IN CHINA AND CAPE VERDE - Moreira, Jaelsa Mira Gonçalves; Shikui, Dong (European Scientific Journal, ESJ, 2014)
Climate change is a real and urgent challenge that is already affecting people and the environment worldwide. Significant changes are occurring on Earth, including increasing air and ocean temperatures, widespread melting of snow and ice, and rising sea levels. Biodiversity loss and ecosystems degradation are being accelerated by climate change. The link between biodiversity conservation and climate change flow both ways: Biodiversity conservation increases the resilience of the physical and biological systems to changing environmental conditions and changes in climatic variables as genetically rich populations and species-rich ecosystems have greater potential for adaptation. This study aimed to find out how climate change affects the choice of instruments used to promote biological conservation in Cape Verde and China, to compare the policies and measures for Climate Change: adaptation and mitigation existent in both countries with respect to their applicability and sustainability. The findings of this study show that Cape Verde and China need more efforts to adapting and mitigating the impacts of climate change. Some progress has been made in promoting biodiversity conservation coping to climate change as well in both countries, but more improvements are required to sustain it and to get the sustainable development.